2) Rearrange the Pythagorean Theorem to solve first for c and then y.
![2 Rearrange the Pythagorean Theorem to solve first for c and then y class=](https://us-static.z-dn.net/files/dd6/80cd0767d546d6cab35fb5ebf58c5e7f.png)
Answer:
[tex]x=z-\sqrt{-y} , or, x^2=z^2-y^2\\y=z-\sqrt{-x}, or, y^2=z^2-x^2[/tex]
Step-by-step explanation:
I can't do much except put the Pythagorean theorem in terms of y or x.
All I did was isolate x or y by subtracting the, x or y variable from each side.
[tex]-(y^2)+x^2 +y^2=z^2-(x^2)\\-(y^2)+x^2 +y^2=z^2-(y^2)[/tex]
Which tuns it into:
[tex]x^2=z^2-y^2\\y^2=z^2-x^2[/tex]
And I isolated further by squaring each side, but squaring negative number is difficult and causes imaginary numbers so I just think it should stay as all of them to the power of two.